The Development of Interactive Learning Media Using the Canva Application on Pancasila Values Material in Class III at SDN 16 Koto Baru - Susilawati, Wiwik Okta; Nanda, Dodi Widia; Fitriah, Fai'zatul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to produce interactive learning media using the canva application on Pancasila values material in grade III, in order to add to the learning media that already exists in schools and produce interactive learning media by using the canpa application on grade III Pancasila values material that is valid, practical, and effective so that it can improve student learning outcomes at SDN 16 Koto Baru. Interactive media using the Canva application so as to make the media interesting. The development model used is the 4-D model, namely define, design, develop, and disseminate. Based on the results of validation by fifteen validators, namely validators of language, materials, graphics, teaching modules, effectiveness questions obtained an average score of 84.70% with a very valid category, practicality results by grade III teachers and students obtained a percentage of 94.72% with a very practical category, while the results of the effectiveness test in the form of question tests were obtained with an average of 90% complete in class III A with a very effective category. Meanwhile, in class III B, the distribution obtained an average of 89.74% is categorized as very effective.